The safety and treatment response of combination therapy of radioimmunotherapy and radiofrequency ablation for solid tumor: a study in vivo. - Shu-Guang Zheng; Hui-Xiong Xu; Le-Hang Guo; Lin-Na Liu; Feng Lu (PLoS ONE)
Objection To investigate the safety and treatment response of radioimmunotherapy (RIT) in combination with radiofrequency ablation (RFA) for the treatment of VX2 tumor on rabbit. Materials and methods A total of 36 rabbits bearing VX2 tumor on the thigh were randomly assigned into 3 groups (group I: 1-2 cm; group II: 2-3 cm; group III: 3-4 cm) and 4 subgroups (A: as control, just puncture the tumor using the RFA electrode without power output; B: RFA alone; C: 131I-chTNT intratumoral injection alone; D: RFA+131I-chTNT intratumoral injection 3 days later). The variation of blood assay, weight and survival among different groups and subgroups were used to assess the treatment safety. Ultrasound (US) was used to monitor and assess the tumor response after treatment. Results According to the results of the weight and the blood assay among different groups, subgroups, and at two time points (one day before and the 16th day after treatment), no damages to the liver, kidney function and myelosuppression resulting from the treatment were found. No significant differences in survivals among the four subgroups (p = 0.087) were found. In addition, 131I-chTNT did not show significant inhibition effect on VX2 tumor progression according to US measurements. Conclusion 131I-chTNT intratumoral injection alone or in combination with RFA is relatively safe for rabbit without significant toxicity and shows no significant effect on the survival. The treatment response is not as satisfactory as anticipated.